Surrogacy in South Africa. Is there a need to amend laws on remunerated surrogacy? - Musvavairi, Ruvimbo (Department of Private Law, 2024)
The issue of surrogacy is gaining prominence, because of the rise of infertility in South Africa and globally. The availability of new technological innovations and improvements, shortage of children for adoption and the desire to have a child who is genetically related to the parents is prompting and increasing number of infertile couples to resort to surrogacy. One of the pertinent issues relates to the remuneration of the surrogate mother. The main purpose of this study has been to determine whether there is any need to amend the current laws on surrogacy in South Africa to include remuneration for work rendered by the surrogate mother through pregnancy and childbirth. From this understanding, this area remains relevant and needs attention. Notwithstanding the potential gains that may be made by amending the laws on remunerated surrogacy, some scholars have expressed their objections and concerns that it gives rise to challenging legal, cultural, ethical, and moral issues, including exploitation, dehumanisation, marketing of surrogate mothers, exploitation and sale of children, and psychological harm and creation of black market. However, some scholars argue that remunerated surrogacy does not amount to the sale of children or the exploitation of children because the payment to the surrogate mother is not for the transfer of the child and the rights from the surrogate mother to the commissioning parents, but rather for the services rendered by the surrogate mother and for the pain and suffering endured during pregnancy and childbirth. Since the issue of remunerated surrogacy is contentious not only in South Africa but internationally, the research examines illustrative examples from selected foreign jurisdictions with different approaches to remunerated surrogacy, such as India, Uganda and California. The main argument that the study puts forth is that surrogacy laws should be amended to accommodate remunerated surrogacy, for instances where the surrogate mother is being compensated for the services that she rendered. Remunerated surrogacy agreements must be carefully regulated to avoid the dangers of permitting wholesale commercial surrogacy, resulting in the commodification of children and the exploitation of women. Ideally, the surrogate agreement between the parties and the terms of the agreement must include the legal, financial and contractual rights that will bind the parties to the agreement. The agreements must be mutually beneficial to the parties (child, surrogate mother and commissioning parents) and couched in a way that will provide proper protection to the parties of the surrogacy agreements. The regulations must be in a way that protects the best interests of the child.